Agricultural Implications of the Fukushima Nuclear Accident 2016
DOI: 10.1007/978-4-431-55828-6_17
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Nuclear Power Plant Accident and the Start of Trial Operations in Fukushima Fisheries

Abstract: The large-scale release of radioactive substances from the Fukushima Daiichi Nuclear Power Plant operated by the Tokyo Electric Power Company in March 2011 caused significant damage to local fisheries. The Fukushima Prefectural Federation of Fisheries Cooperative Associations immediately suspended all commercial fishing activities within Fukushima. The national government issued instructions prohibiting the sale of certain marine products caught in the waters off Fukushima Prefecture due to food safety concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…However, the Japanese and the Fukushima prefectural governments did not revoke the fishing licenses in Fukushima Prefecture, because the Fukushima FCA voluntarily continued to stop the fishing operations off Fukushima for the food safety from March 15, 2011 by the monthly update. In February 2012, the Fukushima FCA established the Fukushima Prefectural Fisheries Reconstruction Committee (Fukushima FRC) with external experts in order to reconstruct the fishery industry and restart the fishing operation off Fukushima [10].…”
Section: Trial Fishing Operations In Fukushimamentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Japanese and the Fukushima prefectural governments did not revoke the fishing licenses in Fukushima Prefecture, because the Fukushima FCA voluntarily continued to stop the fishing operations off Fukushima for the food safety from March 15, 2011 by the monthly update. In February 2012, the Fukushima FCA established the Fukushima Prefectural Fisheries Reconstruction Committee (Fukushima FRC) with external experts in order to reconstruct the fishery industry and restart the fishing operation off Fukushima [10].…”
Section: Trial Fishing Operations In Fukushimamentioning
confidence: 99%
“…In June 2012, based on the advice of the Fukushima FRC, the Fukushima FCA decided to carry out the trial fishing operation off Fukushima. The trial fishing operation has several limitations: the target species, the fishing methods, the number of days a week for operation, landing ports, the amount of landed fishes, the number of vessels involved in operations and the areas for operations [10]. The areas for the trial fishing operations are shown in Fig.…”
Section: Trial Fishing Operations In Fukushimamentioning
confidence: 99%
See 1 more Smart Citation
“…After March 12th, the large-scale release of radioactive substances from the Fukushima Dai-ichi Nuclear Power Plant occurred. On March 15th, 2011, the Fukushima Prefectural Federation of Fisheries Cooperative Association (hereafter referred to as the Fukushima FCA) voluntarily stopped fishing operations in the waters inside of Fukushima Prefecture (Yagi 2014(Yagi , 2016. Some fishing activities in the prefectures neighboring Fukushima (namely Miyagi and Ibaraki) were also suspended after the Fukushima disaster, but most of these were subsequently lifted within 2 years (Ibaraki Prefecture 2014; Miyagi Prefecture 2014).…”
Section: Limited Resumption Of Fishing In Fukushima Watersmentioning
confidence: 99%
“…Some fishing activities in the prefectures neighboring Fukushima (namely Miyagi and Ibaraki) were also suspended after the Fukushima disaster, but most of these were subsequently lifted within 2 years (Ibaraki Prefecture 2014; Miyagi Prefecture 2014). Neither the national nor the prefectural governments revoked fishing licenses in Fukushima (Yagi 2016). However, the national government did provide legally binding sales prohibitions on certain marine products caught in the waters off Fukushima Prefecture based on food safety requirements (Yagi 2016).…”
Section: Limited Resumption Of Fishing In Fukushima Watersmentioning
confidence: 99%